2008
DOI: 10.1002/eat.20550
|View full text |Cite
|
Sign up to set email alerts
|

Timing and prediction of relapse in a transdiagnostic eating disorder sample

Abstract: Clinical recommendations based on these data include encouraging clients to adopt the recommended behavioral changes immediately at the beginning of treatment, and to make complete symptom control a priority. In addition, addressing weight-related self-evaluation and teaching clients to detach from this schema that connects weight/shape with self-esteem may be an effective and feasible step toward relapse prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 38 publications
3
83
1
Order By: Relevance
“…Additionally, given that failure to respond early to treatment may also be a risk factor for less favourable outcomes in the longer term, 46,47 identifying those individuals who fail to respond early in treatment could help to ensure that more intensive follow-up and intervention is conducted where appropriate.…”
Section: Implications For Treatmentmentioning
confidence: 98%
“…Additionally, given that failure to respond early to treatment may also be a risk factor for less favourable outcomes in the longer term, 46,47 identifying those individuals who fail to respond early in treatment could help to ensure that more intensive follow-up and intervention is conducted where appropriate.…”
Section: Implications For Treatmentmentioning
confidence: 98%
“…Recent findings have indicated that ED-NOS represents 60% of all eating disorder cases that present to outpatient services (Turner & Bryant-Waugh, 2004) and that the duration and severity of ED-NOS are similar to AN and BN (Fairburn & Bohn, 2005). The transdiagnostic model and treatment of eating disorders conceptualizes AN, BN, and ED-NOS as a single unitary diagnostic category because of similarities between the groups and because migration between the groups is common (Fairburn, Cooper, & Shafran, 2003;McFarlane, Olmstead, Trottier, 2008).…”
Section: Participantsmentioning
confidence: 99%
“…Similarly, patients with BN who rapidly normalized their eating within the first four to six weeks of treatment had lower rates of binge eating and vomiting at post-treatment (Wilson, Fairburn, Agras, Walsh, & Kraemer, 2002). In transdiagnostic eating disorder samples, rapid reduction in the cognitive psychopathology of eating disorders (Raykos, Watson, Fursland, Byrne, & Nathan, 2013) and rapid normalization of eating (McFarlane, Olmsted, & Trottier, 2008) were associated with better remission rates and lower relapse rates, respectively. Despite the fact that rapid response to treatment has consistently been associated with higher remission and lower relapse rates, this literature is limited by the use of many different operational definitions of rapid response.…”
mentioning
confidence: 93%
“…Operational definitions of key constructs critically affect rates of relapse and affect interpretability and comparability of findings (Olmsted, Kaplan, & Rockert, 2005). Research on rapid response has defined the "initial period" of treatment as the first week (Zunker et al, 2010), first three weeks (McFarlane et al, 2008;Vaz et al, 2014), first four weeks (Agras et al, 2000;Fairburn et al, 2004;Grilo et al, 2006;McFarlane, MacDonald, Royal, & Olmsted, 2013;Olmsted et al, 1996, in press;Wilson et al, 2002;Zunker et al, 2010), first five weeks (Raykos et al, 2013), and first six weeks (le Grange et al, 2008;Wilson et al, 2002). The operationalization of response itself has also varied widely to include binge eating and/or vomiting reduction ranging from 49% to 85% within the first four to six weeks (i.e., Agras et al, 2000;Fairburn et al, 2004;Grilo et al, 2006;le Grange et al, 2008;Zunker et al, 2010).…”
mentioning
confidence: 97%